PENGELOLAAN DANAU SITU GEDE DAN HUTAN PENELITIAN DRAMAGA SEBAGAI KAWASAN EKOWISATA - Muthiannisa Umarputri; Parino Rahardjo (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Situ Gede is a natural lake surrounded by Dramaga Research Forest and has the potential to become an object of ecotourism studies. However, there are still problems in the area, including the management of facilities and infrastructure which if ignored can threaten the balance of the ecosystem. In order for better management of the area, it is necessary to know the potential and problems in the region and then manage it as an ecotourism area so that it attracts people to visit but the ecosystem in it is maintained and becomes a sustainable tourism. There are aspects that are considered for tourism (Fandeli, 1995), namely attractions (attraction), amenities (facilities) and accessibility. For ecotourism, the necessary components related to management are from aspects of conservation, entertainment, economy, community participation, education and local wisdom based on Domestic Government Regulation No.33 of 2009 Article 3 and for basic management principles (Wurtzebach & Miles, 1984) consisting of 3E (Efficient, Effective, Economical) plus 4C (Complementary, Competitive, Comfortable, Convenience) produces MPAM (Profitable, Marketable, Adaptable, Manageable) and considers management elements such as organization, management, human resources, facilities and infrastructure, tourist attraction and promotion. By using quantitative and qualitative research and research methods in the form of field surveys, interviews, and collection of related documents and then analyzing the conditions of existing management, best practices, carrying capacity and management strategies, recommendations can be generated from management aspects and their eco-aspects. AbstrakSitu Gede merupakan situ atau danau alami yang dikelilingi oleh Hutan Penelitian Dramaga dan berpotensi untuk menjadi objek studi ekowisata. Namun masih terdapat permasalahan pada kawasan tersebut, di antaranya pengelolaan sarana dan prasarana yang bila didiamkan dapat mengancam keseimbangan ekosistem. Agar pengelolaan kawasan menjadi lebih baik, perlu diketahui potensi dan masalah pada kawasan untuk kemudian dibuat pengelolaannya sebagai kawasan ekowisata agar menarik minat masyarakat untuk berkunjung namun ekosistem di dalamnya tetap terjaga dan menjadi wisata berkelanjutan. Terdapat aspek yang diperhatikan untuk pariwisata (Fandeli, 1995) yaitu atraksi (daya tarik), amenitas (fasilitas) dan aksesibilitas. Untuk ekowisata, komponen yang diperlukan terkait pengelolaan ialah dari aspek konservasi, hiburan, ekonomi, partisipasi masyarakat, edukasi dan kearifan lokal berdasarkan Peraturan Pemerintah Dalam Negeri No.33 Tahun 2009 Pasal 3 dan untuk prinsip dasar pengelolaan (Wurtzebach & Miles, 1984) terdiri dari 3E (Efisien, Efektif, Ekonomis) ditambah 4C (Complementary, Competitive, Comfortable, Convenience) menghasilkan MPAM (Profitable, Marketable, Adaptable, Manageable) dan memerhatikan unsur pengelolaan seperti organisasi, manajemen, sumber daya manusia, sarana dan prasarana, daya tarik wisatawan dan promosi. Dengan menggunakan penelitian kualiltatif dan kuantitatif serta metode penelitian berupa survei lapangan, wawancara, dan pengumpulan dokumen terkait kemudian menganalisis kondisi pengelolaan eksisting, best practices, daya dukung serta strategi pengelolaan maka dapat dihasilkan rekomendasi dari aspek pengelolaan serta aspek ekowisatanya.